HUBUNGAN KEBIASAAN SARAPAN, TINGKAT KECUKUPAN ENERGI DAN GIZI MAKRO DENGAN STATUS GIZI PADA SISWA PONDOK PESANTREN AL-FATTAH BUDURAN, SIDOARJO - Hanik Rosida (Media Gizi Indonesia, 2017)
Nutrition plays vital role in the improvement of academic achievement and growth for adolescent. Adolescent have many activity, therefore needs balance nutritional intake. The aimed of this research was analyzed the relation between breakfast habit, macronutrient adequacy level, with nutritional status of adolescent at Al-Fattah Boarding School, Buduran, Sidoarjo. This research was an analytic observational with cross sectional design. The sample of this research was 72 active students of Al- Fattah Boarding School. Breakfast habit and food consumption were collected through food recall 24 hours. Nutritional status determine by Body Mass Index for Age (BAZ). The logistic regression was used to analyze the data. The results showed that majority of respondent has age 13-15 years (75.6%), male (52.8%) and normal nutritional status (52.8%). There was a relation between breakfast habit, carbohydrate and protein adequacy with nutritional status. There was no relation between energy and fat adequacy with nutritional status.